2002
DOI: 10.1095/biolreprod66.2.429
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Adenosine Triphosphate Stimulates Acrosomal Exocytosis in Bovine Spermatozoa via P2 Purinoceptor1

Abstract: The presence of ATP in the genital tract fluid of mammals provokes questions regarding its function in the fertilization process. We investigated the effect of extracellular ATP (ATPe) on the activation of bovine spermatozoa. A signal transduction mechanism for ATP involving the receptor-mediated release of second messengers is described. Treatment of spermatozoa with ATP, uridine triphosphate (UTP), or 2-methylthio-ATP resulted in a concentration-dependent increase of acrosomal exocytosis, whereas treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 56 publications
3
41
0
Order By: Relevance
“…In fact, our earlier study in pancreatic duct cells has showed that NYD-SP27 acts as a physical PLC inhibitor [7]. In this study, Ca 2+ mobilization in sperm induced by either extracellular ATP or progesterone, whose receptors are known to be coupled to PLC [13,[21][22][23], was inhibited by both PLC inhibitor and retention of mNYD-SP27 in sperm by its antiserum. Taken together, these observations show that capacitation is made possible only if NYD-SP27, an intrinsic decapacitation factor, is removed from sperm.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In fact, our earlier study in pancreatic duct cells has showed that NYD-SP27 acts as a physical PLC inhibitor [7]. In this study, Ca 2+ mobilization in sperm induced by either extracellular ATP or progesterone, whose receptors are known to be coupled to PLC [13,[21][22][23], was inhibited by both PLC inhibitor and retention of mNYD-SP27 in sperm by its antiserum. Taken together, these observations show that capacitation is made possible only if NYD-SP27, an intrinsic decapacitation factor, is removed from sperm.…”
Section: Discussionmentioning
confidence: 72%
“…ATP and progesterone have been considered physiological agonists of the PI-PLC pathway [13,21,22] and can induce the acrosome reaction in vitro through different pathways and mechanisms. Our study indeed shows that although NYD-SP27 was retained in sperm, ATP and progesterone show differential effects on the number of acrosome-reacted sperm (Figures 7 and 8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations